Metastatic Merkel cell carcinoma. - Levato, E.; Troia, M. (European Journal of Pediatric Dermatology, 2014)
Case report. A 91-year-old woman was first observed due to a neoformation of the leg dating from 10 years according to the history. The physical examination showed a nodule of about 1 cm in diameter, with eroded surface, non-tender, mobile on the deep layers (Fig. 2), leading to diagnose squamous cell cr. The patient asked to postpone the removal of a couple of months. 2 months later the lesion had changed significantly. The physical examination showed a 3 cm ulcerated plaque and in the proximal skin below the knee about twenty asymptomatic nodules of 3-9 mm (Fig. 1) covered by intact skin, hard-elastic and movable on the superficial and deep layers. A biopsy of the primary lesion and removal of a metastatic nodule was performed. The histology showed in the ulcerated plaque and in the secondary nodule a proliferation of small basophilic cells (Fig. 3) with many mitoses and invasion of vessels. Immunohistochemistry confirmed the suspicion of metastatic Merkel cell cr. The patient began radiation therapy.